Hericium erinaceus mycelium and its small bioactive compounds promote oligodendrocyte maturation with an increase in myelin basic protein - Huang, Hui-Ting; Ho, Chia-Hsin; Sung, Hsin-Yu; Lee, Li-Ya; Chen, Wan-Ping; Chen, Yu-Wen; Chen, Chin-Chu; Yang, Chung-Shi; Tzeng, Shun-Fen (Scientific reports, 2021)
Oligodendrocytes (OLs), myelin-producing glia in the central nervous system (CNS), produce a myelin extension that enwraps axons to facilitate action potential propagation. An effective approach to induce oligodendrogenesis and myelination is important to foster CNS development and promote myelin repair in neurological diseases. Hericium ( H. ) erinaceus , an edible and culinary-medicinal mushroom, has been characterized as having neuroprotective activities. However, its effect on OL differentiation has not yet been uncovered. In this study using oligodendrocyte precursor cell (OPC) cultures and an ex vivo cerebellar slice system, we found that the extract from H. erinaceus mycelium (HEM) not only promoted the differentiation of OPCs to OLs in the differentiation medium, but also increased the level of myelin basic protein (MBP) on neuronal fibers. Moreover, daily oral administration of HEM into neonatal rat pups for 7 days enhanced MBP expression and OLs in the corpus callosum of the postnatal rat brain. The effect of HEM-derived bioactive compounds, the diterpenoid xylosides erinacine A (HeA) and HeC and a sesterterpene with 5 isoprene units called HeS, were further evaluated. The results showed that HeA and HeS more potently stimulated MBP expression in OLs and increased the number of OLs. Moreover, overlap between MBP immunoreactivity and neuronal fibers in cultured cerebellar tissue slices was significantly increased in the presence of HeA and HeS. In summary, our findings indicate that HEM extract and its ingredients HeA and HeS display promising functional effects and promote OL maturation, providing insights into their potential for myelination in neurodevelopmental disorders.